Susceptibility to Temephos and Spinosad in Aedes aegypti (Diptera: Culicidae) From Puerto Rico. Issue 5 (20th June 2016) - Del Rio-Galvan, Samanta L.; Flores, Adriana E.; Barrera, Roberto; Lopez-Monroy, Beatriz; Felix, Gilberto; Amador, Manuel; Ponce-Garcia, Gustavo
Abstract: We examined the susceptibility to temephos and spinosad (Natular EC) of eight Aedes aegypti (L.) populations from Puerto Rico, following WHO method (WHO 2005). Enzyme activity was measured for alpha- and beta-esterases, multiple function oxidases, glutathione-s-transferases, and insensitive acetylcholinesterase and was tested for correlation with the susceptibility level. The results showed that larval populations from Puerto Rico obtained during 2014 were found to be susceptible to both larvicides, with low (resistance factor) RRLC50 values (<5 fold) and altered and incipiently altered enzyme expression for all populations, except the insensitive acetylcholinesterase enzyme, where only the population of Ponce showed overexpression (53.3%) above the threshold established with the New Orleans susceptible strain. We recommend the use of both larvicides for mosquito control in the study area and encourage further susceptibility monitoring.